1993
DOI: 10.1007/978-94-017-3450-9_22
|View full text |Cite
|
Sign up to set email alerts
|

Yolk utilization in Scyliorhinus canicula, an oviparous dogfish

Abstract: SynopsisUsing plastic embedding techniques and semithin sections, in order to overcome the difficult sectioning of yolky eggs, we have been able to carry out histological study of the external yolksac from fertilization until birth in the oviparous dogfish Scyliorhinus canicula. The endoderm and its contacting giant yolk nuclei remained very flat, seemingly inactive, during the larger part of development They became activated only when the external yolksac (EYS) began to shrink. This activation increased along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…Taken together, our findings indicate that urea is produced in the endodermal layer of the YSM, and is then excreted into nearby blood vessels, and subsequently transferred to the embryo in order to maintain a high concentration of urea in the body fluid. Yolk sacs are found in many vertebrates, and the extra-embryonic YSM has been considered to play a key role in the absorption of yolk nutrients (Lambson, 1970;Diez and Davenport, 1990;Lechenault et al, 1993;Zohn and Sarkar, 2010;Bauer et al, 2013). An intriguing finding on the role of the YSM in teleost fish is that it is involved in osmoregulation during early development .…”
Section: Research Articlementioning
confidence: 99%
“…Taken together, our findings indicate that urea is produced in the endodermal layer of the YSM, and is then excreted into nearby blood vessels, and subsequently transferred to the embryo in order to maintain a high concentration of urea in the body fluid. Yolk sacs are found in many vertebrates, and the extra-embryonic YSM has been considered to play a key role in the absorption of yolk nutrients (Lambson, 1970;Diez and Davenport, 1990;Lechenault et al, 1993;Zohn and Sarkar, 2010;Bauer et al, 2013). An intriguing finding on the role of the YSM in teleost fish is that it is involved in osmoregulation during early development .…”
Section: Research Articlementioning
confidence: 99%
“…Oviparous species and lecithotrophic viviparous species continue to be yolk reliant throughout gestation. Other viviparous species display diverse methods of providing maternally derived nutrients either through uterine secretions (histotrophy), ova (ovatrophy), siblings (intrauterine cannibalism or adelphotrophy), or placental transfer (placentatrophy) (TeWinkel, 1943;Von Bonde, 1945;TeWinkel, 1963;Jollie and Jollie, 1967b;Baranes and Wendling, 1981;Wourms, 1983, 1984;Hamlett, 1987Hamlett, , 1989bHamlett, , 1993Hamlett et al, 1993c;Lechenault et al, 1993) Eight modes of reproduction have been described for viviparous chondrichthyans. Lecithotrophic viviparity is a reproductive mode in which no placenta is formed, the uterine mucosa develops vascularized flaps, folds, or villi and the embryos rely on yolk sequestered in the yolk sac that persists throughout gestation.…”
mentioning
confidence: 98%
“…Lechenault et al (1993) reported that the liver constituted only 4.8-6.8% of the total body wet mass of Scyliorhinus canicula (an oviparous dogfish) neonates. If one assumes that all of the CPSase III activity is localized in the liver of R. erinacea embryos, then we have severely underestimated the hepatic CPSase III activity in embryos.…”
Section: Table·3 Glutamine Synthetase (Gsase) Carbamoyl Phosphate Smentioning
confidence: 99%